Association between VEGF genetic variants and diabetic foot ulcer in Chinese Han population: A case–control study. Issue 20 (May 2018) - Li, Xiaolei; Lu, Yonghua; Wei, Peng
Abstract : Abstract: The aim of this study was to investigate the association of vascular endothelial growth factor (VEGF) gene polymorphisms with diabetic foot ulcer (DFU) susceptibility in a Chinese Han population. Around 88 type 2 diabetes mellitus (T2DM) patients without DFU and 97 T2DM patients with DFU were enrolled in this study. A total of 103 age and gender matched healthy individuals were recruited as healthy control. VEGF gene polymorphisms rs699947 and rs13207351 were analyzed by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) method. Odds ratio (OR) with 95% confidence interval (CI) was calculated to assess the association between VEGF gene polymorphisms and DFU risk. The frequency of AA and AC genotypes of rs699947 were lower in DFU patients than that in healthy controls ( P = .020, P = .031), suggesting that AC and AA genotypes were negatively associated with DFU risk originating from healthy individuals (OR = 0.496, 95%CI = 0.274–0.899; OR = 0.130, 95%CI = 0.015–1.112). Significantly decreased trend of rs699947 A allele was observed in DFU patients when compared to the controls ( P = .004), suggesting A allele was distinctly correlated with decreased DFU risk (OR = 0.490, 95%CI = 0.298–0.804). But no significant differences were detected in rs13207351 genotype and allele distributions between patients and control groups ( P > .05). Individuals carrying VEGF rs699947 A allele show low susceptibility to DFU in the Chinese Han population.